Aplikasi Game Cerita Rakyat Bali Sebagai Sarana Pendidikan Karakter Anak Berbasis Mobile - Ardiana, Dewa Putu Yudhi; Pandawana, I Dewa Gede Agung (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 3 Desember 2017, 2017)
Folklore has a value of local wisdom that can be used in character learning for children. the delivery of folklore to children is mostly done by parents through telling stories. the phenomenon of less popular folklore by children one of them due to lack of time parents to convey the story . This study goals to transform Balinese folklore into mobile-based game applications, in order to make it more interesting, further, it could be use as a means of character education teaching gained from the local wisdom of folklore and introducing local culture to children. Moral messages that want to be presented in this game is the right promise, honest and helpful through crukcuk kuning story, i kekua and i lacur. Based on the questionnaires as the assessment method could obtained the application of the Bali Folk Story Game categorized well.